Вербалізація полярних емотивних концептів LOVE – HATE у британському художньому дискурсі ХХ ст - Малиненко, Олександра Євгенівна; Malynenko, A. Y. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті описано особливості вербалізації опозиції емотивних концептів LOVE – HATE у британському художньому дискурсі ХХ ст. Емотивні концепти LOVE та HATE репрезентують одну із ключових опо¬зицій емоційної картини світу. Специфіку мовної об’єктивації цих концептів розглянуто в межах лінгво¬когні¬тивної парадигми, яка дає змогу дослідити віддзеркалення емоцій у мові крізь призму людського сприйняття. Встановлено семантичні та частиномовні характеристики засобів вираження концептів LOVE – HATE. The article deals with the semantic and part-of-speech characteristics of emotive opposition of concepts LOVE – HATE verbalization in the British literary discourse in XX century. Emotive concepts LOVE and HATE are considered to be one of the key oppositions of emotional worldview. The verbal representation of the concepts in question is viewed within linguocognitive paradigm that enables to investigate the language reflection of emotions through an individual’s perception. Semantic and part-of-speech distinctive features of the concepts LOVE – HATE verbalization means are analyzed. The contexts with the emotive concept LOVE prevail over the contexts with the emotive concept HATE. The convergences and the divergences of the semantic types verbalization means of the concepts under analysis are determined. The productivity of different language means in the concepts’ actualization in the literary discourse is described.
Verbalization of Polar Emotive Concepts LOVE – HATE in XX century British Literary Discourse
Keywords: категорія емотивності; category of emotivity; концепт; concept; емотивний концепт; emotive concept